If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18x + yz = 19 Solving 18x + yz = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1yz' to each side of the equation. 18x + yz + -1yz = 19 + -1yz Combine like terms: yz + -1yz = 0 18x + 0 = 19 + -1yz 18x = 19 + -1yz Divide each side by '18'. x = 1.055555556 + -0.05555555556yz Simplifying x = 1.055555556 + -0.05555555556yz
| 2y-2=15 | | (4x^2+4x+6)(7x+5)=0 | | 2+m=12 | | -3+k=-3 | | (2x^2+5x+5)(4x-3)=0 | | -2=x+1 | | -5a=-55 | | k-10=-17 | | (8x^2+6x+8)(6x-5)=0 | | d-4=5 | | x/-7=-4 | | t+9=-1 | | 3=k+8 | | b+10=14 | | 7=b+4 | | d-8=-5 | | 6=w+7 | | (5x^2+2x+8)(7x-6)=0 | | 5(-7+8v)-3(2+3v)=-72 | | 4+k=8 | | 6+d=-3 | | n+1=0 | | t/2=-1 | | t+4=-4 | | (5x^2-4x-1)(7x^2+9x+8)=0 | | 75x+45(289-x)=17895 | | 10+t=6 | | -10+a=-20 | | 5=w+3 | | k-10=-8 | | a+2=-1 | | Y=2/3x-25/3 |